Effective hospital management practice for meeting customers' needs and expectations - Wan Su, Kamaruzaman (2002)
When a person is sick and decides to seek treatment from a hospital, few questions run in his mind which we call them 'the customers' needs and expectations'. He will be thinking whether the treatment he needs is readily available in the hospital. Are the people there friendly? Will he be safe and not lost in the compound of the hospital? How long he will wait to see the doctor and to take medications? How much is the hospital fees? Will his sickness improve with treatment? His perception of the hospital services sometime differs from what we understand. We produce a list of what we promise to do in the form of a patient's charter, but sometimes this is not what the patient needs or expects. The gap between the services the hospital can offer and the needs and expectations of the patient will determine the level of satisfaction. Patient will be satisfied if he gets all that he needs. He will be more satisfied if the hospitality rendered to him is beyond his expectation. Hence hospital managers have to know the customers' needs and expectations before they can plan effective hospital management practice to meet these needs and expectations.